Titanium addition influences antibacterial activity of bioactive glass coatings on metallic implants - Omar Rodriguez; Wendy Stone; Emil H. Schemitsch; Paul Zalzal; Stephen Waldman; Marcello Papini; Mark R. Towler (Heliyon, 2017)
In an attempt to combat the possibility of bacterial infection and insufficient bone growth around metallic, surgical implants, bioactive glasses may be employed as coatings. In this work, silica-based and borate-based glass series were synthesized for this purpose and subsequently characterized in terms of antibacterial behavior, solubility and cytotoxicity. Borate-based glasses were found to exhibit significantly superior antibacterial properties and increased solubility compared to their silica-based counterparts, with BRT0 and BRT3 (borate-based glasses with 0 and 15 mol% of titanium dioxide incorporated, respectively) outperforming the remainder of the glasses, both borate and silicate based, in these respects. Atomic Absorption Spectroscopy confirmed the release of zinc ions (Zn2+), which has been linked to the antibacterial abilities of glasses SRT0, BRT0 and BRT3, with inhibition effectively achieved at concentrations lower than 0.7 ppm. In vitro cytotoxicity studies using MC3T3-E1 osteoblasts confirmed that cell proliferation was affected by all glasses in this study, with decreased proliferation attributed to a faster release of sodium ions over calcium ions in both glass series, factor known to slow cell proliferation in vitro.